Caracterização farmacológica dos efeitos induzidos pelo complexo de rutênio cis-[Ru(H-dcbpy-)2(Cl)(NO2- )] e Nitroprussiato de Sódio na disfunção endotelial - Buzinari, Tereza Cristina (Universidade Federal de São Carlos, 2016)
Endothelial dysfunction has been considered a marker for the presence of cardiovascular disease. It is characterized by decreased release of vasodilatory factors and increased of vasoconstrictors factors. Nitric oxide (NO) is the main endogenous vasodilator molecule that regulates the vascular tone and homeostasis. Decrease in the bioavailability of NO can be caused by a variaty of factors, including the increase in the production of superoxide radical O2 •-. The production of O2 •- can be stimulated by angiotensin II, by the enzyme complex of the NADPH oxidase activation. Thus, the objective of this work was to study the effects induced by ruthenium complex cis-[Ru(H-dcbpy-)2(Cl)(NO2 -)] (DCBPY) and sodium nitroprusside (SNP) in endothelial dysfunction model, as well as perform the pharmacological characterization of the dependent effects removal of O2 •- and release of nitric oxide (NO) induced by these drugs. Normotensive (2K) and hypertensive (2K-1C) wistar rats were used. Aortic rings with intact endothelium were placed in a myograph and incubated with DCBPY: 0.1; 1.0 ou 10 μM ou com SNP: 0.1; 1.0 ou 10 nM during 30 minutes. Curves concentration-effect of acetylcholine (ACh) were built where it was possible to analyze all concentrations DCBPY and NPS improved relaxation induced by ACh. NO was measured intracellular (for DAF-2DA probe) in HUVEC treated with 0.1 μM of DCBPY, 0.1 nM a SNP and 0.1 μM DETA-NO. It was not detected NO release of the compounds DCBPY [0.1 μM] and SNP [0.1 nM]. It also evaluated the release of NO compound DCBPY using an electrode selective for NO. The compound DCBPY spontaneously release NO in solution form concentrationdependent, starting from 10 μM concentration. DCBPY released more NO in the presence of cells. This could be due to the reduction of the compound by reducing cell. Intracellular detection of superoxide radical (O2 •-) was obtained by using the fluorescent probe (DHE). Our results show that treatment of cells with DCBPY [0.1 μM] and SNP [0.1 nM] decreased the fluorescence intensity cells stimulated with angiotensin II. Thus, it is suggested that DCBPY and SNP at a concentration which does not release NO, inside the cells, they are capable of attenuating endothelial dysfunction by inactivating superoxide.
Keywords: Óxido nítrico; Disfunção endotelial; Radical superóxido; DCBPY; NPS; CIENCIAS BIOLOGICAS::FISIOLOGIA